Thinking Religion and Religious Studies - Milani, Milad (Marburg journal of religion, 2025)
This article argues religious studies is a discipline specifically designed for answering the big questions about religion. The comparative and general study of religion is what emerges when scholarship abandons the big questions about religion. This occurs first by the field's distancing from theology and later philosophy. Historical and phenomenological approaches present religious studies as a pluralistic and multidisciplinary research field, whilst arguably it is originally polymethodic. The difference, I argue, is that the religious studies discipline is better defined by a multiple methods approach rather than a disciplinary hybridity. I make my argument by discussing the philosophical method of "thinking" as necessary to reclaim for religious studies and specifically making the case for thinking as a key method for religious studies research.